Developing Hand Puppet Video as Media for Teaching and Learning Speaking in Senior High School - Zukhruf Irfan Maulana; Dian Fadhilawati; Adin Fauzi (Jurnal Sinestesia, 2022)
The objectives of this study are to establish the model of hand puppet video for teaching and learning speaking in Senior High school that focused on narrative text, to discover the feasibility of hand puppet video for teaching and learning speaking, and to know the teacher’s and student’s responses toward the use of hand puppet video for teaching and learning speaking in senior high school. This study adapted Sugiyono's models that include some steps such as: analyzing potentials, problems, and solutions, Design and development, Experts Validation and revision, Teachers’ and students’ perception, evaluation and revision, and Final product and publication. The finding of this research showed that 1) the developed hand puppet video for teaching learning speaking covered three parts, they were; part 1 (introduction), part 2 (video), and part 3 (exercise) with additional setting features. Part 1 (introduction) consists of a description, material of the narrative text, how to play, and references, Part 2 (video) consists of the narrative stories video in the forms of legend and fable, and Part 3 (exercise) in the form of Retelling the story with the student’s own word. Furthermore, The Hand Puppet Video is also completed with three guide books they are for teachers, students, and the public users 2) The Model Hand Puppet Video was valid to be used as media for teaching and learning speaking n Senior High School, it was revealed by the validation average results from material experts 81, 3 % (very valid) and media experts 88.5% (Very Valid). 3) The teachers and Students showed very positive responses toward the developed product as it is proved by the average results of the questionnaire given to teachers= 87.2% (Very positive), and students’ responses of 87.75% (Very Positive). Referring to the findings, it is suggested for the teachers and students to use the developed product as media for teaching and learning to speak of narrative text in senior high school.